MEDIA SMART TREE UNTUK MENSTIMULASI PERKEMBANGAN MOTORIK HALUS ANAK USIA 3-4 TAHUN: SMART TREE MEDIA TO STIMULATE FINE MOTOR DEVELOPMENT IN CHILDREN AGED 3–4 YEARS - Nur Azizah, Siti; Kusna, Siti Labiba; Puspitasari, Endang (Thufuli, 2022)
Fine motor or subtle movements are specifically controlled by small muscles that must be stimulated. Media Smart Tree is a development medium that stimulates fine motor skills for children aged 3-4 years. Smart tree media aims to stimulate children's fine motor development which is designed to consist of 3 game sides, the first side is the Meronce Educational Game, the second side is a puzzle game, the third side is putting objects in bottles. Smart tree media is made of plywood boards and covered with felt. The development of Smart Tree media uses research and development. Researchers used the Borg and Gall model, which carried out seven of the ten steps of the research procedure. The results of validation with media experts, the following results were obtained: the results of the percentage validity of media experts were 85% with Very Eligible validation criteria, the results of the presentation of material expert validity were 83,3% with Very Eligible validation criteria. From this it can be concluded that the media is feasible to use.